The Role of Islamic Education Policy in the Formation of the Nation's Character in the Era of Globalization - Ade Gunawan; Arum Nuzulur Rohmah; Imam Hanafi; Riskiyah (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
This research aims to see how Islamic education policies play a role in shaping the character of the nation in the era of globalization. The method used is qualitative by studying books and other sources. The findings show that Islamic education policies play an important role as the basis of national morality and identity in the midst of many foreign cultural influences. The implementation of this policy needs to combine religious values with skills needed in the 21st century, such as critical thinking skills and the ability to use technology. Flexible ways are needed to keep Islamic education relevant, including strengthening the curriculum and teachers' abilities. In this way, Islamic education is expected to produce a generation that has a strong character, is able to compete, and still upholds the values of Islamic teachings.